In vitro and in vivo anti‐tumoral effect of curcumin against melanoma cells - Odot, Johann; Albert, Philippe; Carlier, Annie; Tarpin, Michel; Devy, Jérôme; Madoulet, Claudie (International journal of cancer, 2004)
Curcumin, the active ingredient from the spice turmeric (Curcuma longa Linn), is known to be an anti‐oxidant and an anti‐inflammatory agent. It has been demonstrated recently to possess anti‐angiogenic effects and pro‐apoptotic activities against Ehrlich ascites tumor cells. In the current study, curcumin was found to be cytotoxic in vitro for B16‐R melanoma cells resistant to doxorubicin either cultivated as monolayers or grown in three‐dimensional (3‐D) cultures (spheroids). We have demonstrated that the cytotoxic effect observed in the 2 culture types can be related to the induction of programmed cell death. In our in vivo studies, we examined the effectiveness of a prophylactic immune preparation of soluble proteins from B16‐R cells, or a treatment with curcumin as soon as tumoral appearance, alone or in combination, on the murine melanoma B16‐R. The combination treatment resulted in substantial inhibition of growth of B16‐R melanoma, whereas each treatment by itself showed little effect. Moreover, animals receiving the combination therapy exhibited an enhancement of their humoral anti‐soluble B16‐R protein immune response and a significant increase in their median survival time (>82.8% vs. 48.6% and 45.7% respectively for the immunized group and the curcumin‐treated group). Our study shows that curcumin may provide a valuable tool for the development of a therapeutic combination against the melanoma. © 2004 Wiley‐Liss, Inc.